Marital Relationships in George Eliot´s Prose - Koukalová, Veronika (Univerzita Pardubice, 2010)
The topic of this bachelor thesis is analysis of marital relationships described in George Eliot´s prose. Specifically this work deals with three novels - Middlemarch, Silas Marner and The Mill on the Floss. The main object is to compare marital and extra-marital relationships between men and women in terms of morality and the degree of conformity. Further characterize the position and conduct of women in such relationships and opinions of the society about particular partnership. This analysis is preceded by a characterization of the Victorian society focused on Victorian morality, a view of a marriage and a position of women in the nineteenth century. The content of this work will be supported by the chosen secondary literature.
Manželské vztahy v díle George Eliot
Keywords: manželství; postavení žen; George Eliot; Silas Marner; The Mill on the Floss; Middlemarch; marriage; a position of women